The use of narrative in supporting the teaching of socio-scientific issues: a study of teachers' reflections - Levinson, Ralph (2010)
While narratives which integrate aspects of human consciousness can be a powerful instrument in teaching and learning about socio-scientific issues, the science curriculum offers unfruitful grounds for the development of narrative in school students. Learning science and learning about socio-scientific issues are epistemologically distinct activities. The way teachers across the curriculum use narratives suggests that an interdisciplinary approach might be more effective for teaching these issues, particularly where narrative plays a core role. - Apesar das narrativas que integram aspectos da consciência humana poderem constituir um instrumento poderoso no ensino e na aprendizagem sobre questões sociocientíficas, o currículo de ciências oferece pontos de partida pouco frutíferos para o desenvolvimento de narrativas pelos alunos. Aprender ciência e aprender acerca de questões sociocientíficas são actividades epistemologicamente distintas. A forma como os professores de diferentes áreas do espectro curricular utilizam as narrativas sugere que uma abordagem interdisciplinar poderá ser mais eficaz para o ensino destas questões, particularmente onde a narrativa ocupa um papel central.